Leveraging Podcasts to Introduce Medical Students to the Broader Community of Health Care Professionals - Kelsey A. Miller; Tamra Keeney; Allison Fialkowski; Sanjana Srinivasan; Tara A. Singh; Jennifer Kesselheim; Susan Farrell; Cynthia Cooper; Celeste S. Royce (Association of American Medical Colleges, 2021)
Introduction Safe, patient-centered, and cost-effective care requires effective collaboration within interprofessional teams. Education programs for health care professionals are often siloed, providing students with limited interprofessional education (IPE) opportunities to learn from, with, and about other professions. Podcasts offer a novel approach to facilitate IPE, allowing for asynchronous conversations with interprofessional colleagues. Methods We developed four podcasts with various health care professionals for 135 preclinical medical students preparing to transition into clinical rotations. The podcasts were coupled with an hour-long interactive session with the podcast interviewees conducted via videoconference. The curriculum explored the distinct education paths, roles, and responsibilities of various health care disciplines. Strategies for communicating effectively with and learning from interprofessional team members were emphasized. Results There were 197 unique downloads of the podcasts, and 95 students attended the interactive session. Most students reported that the podcasts and follow-up live session enhanced their learning (100% and 98% of students who completed the postcurriculum survey, respectively). Responses to the postcurriculum survey revealed students learned strategies for engaging in productive interprofessional conversations, the importance of leveraging the distinct roles and responsibilities of diverse health professionals, the value of learning from other health professionals, and the use of respectful language. Discussion This IPE curriculum built around podcasts enhances medical student learning and represents an innovative approach to improving access to IPE in a virtual learning environment. This modality can be adapted to meet the needs of a wide spectrum of learners and can be coupled with in-person learning.